Taurine supplementation abates cirrhosis-associated locomotor dysfunction - Heidari, Reza (Clin Exp Hepatol, 2018)
AIM OF THE STUDY: Hepatic encephalopathy and hyperammonemia is a clinical complication associated with liver cirrhosis. The brain is the target organ for ammonia toxicity. Ammonia-induced brain injury is related to oxidative stress, locomotor activity dysfunction, and cognitive deficit, which could lead to permanent brain injury, coma and death if not appropriately managed. There is no promising pharmacological intervention against cirrhosis-associated brain injury. Taurine (TAU) is one of the most abundant amino acids in the human body. Several physiological and pharmacological roles have been attributed to TAU. TAU may act as an antioxidant and is an excellent neuroprotective agent. This study aimed to evaluate the effect of TAU supplementation on cirrhosis-associated locomotor activity disturbances and oxidative stress in the brain. MATERIAL AND METHODS: Rats underwent bile duct ligation (BDL) surgery, and plasma and brain ammonia level, plasma biochemical parameters, and rats’ locomotor function were monitored. Furthermore, brain tissue markers of oxidative stress were assessed. RESULTS: It was found that plasma and brain ammonia was increased, and markers of liver injury were significantly elevated in the cirrhotic group. Impaired locomotor activity was also evident in BDL rats. Moreover, an increase in brain tissue markers of oxidative stress was detected in the brain of cirrhotic animals. It was found that TAU supplementation (50, 100, and 200 mg/kg, gavage) alleviated brain tissue markers of oxidative stress and improved animals’ locomotor activity. CONCLUSIONS: These data suggest that TAU is a potential protective agent against cirrhosis-associated brain injury.